(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of pelvic floor dysfunction (PFD) in women using the Pelvic Floor Distress Inventory-20 (PFDI-20) at Binh Duong General Hospital. Subject and method: A descriptive case-series study was conducted on 77 women diagnosed with PFD from May 2025 to December 2025. Eligible participants were aged ≥18 years, non-pregnant, and had clinically confirmed PFD. Data were collected through interviews, medical records, and the PFDI-20 questionnaire, which evaluates pelvic organ prolapse (POPDI-6), colorectal–anal (CRADI-8), and urinary (UDI-6) symptoms. Variables were summarized using frequencies, percentages, and mean ± standard deviation. Results: The mean age was 46.36 ± 5.57 years, and mean BMI was 22.84 ± 2.78 kg/m². Most participants had a history of vaginal delivery (74.0%) and two childbirths (83.1%). Urinary symptoms were predominant, with stress urinary incontinence reported in 71.4% and overall urinary incontinence in 75.0%. Colorectal–anal symptoms were common, particularly straining during defecation (72.7%) and involuntary loss of gas (66.2%), while fecal incontinence was less frequent (6.5%). Pelvic organ prolapse symptoms were uncommon, with vaginal bulge reported in 3.9%. Pelvic pain was rare (1.3%). Overall, symptom burden was mainly driven by urinary and defecatory dysfunction. Conclusion: Pelvic floor dysfunction in this cohort was characterized predominantly by urinary incontinence and colorectal–anal symptoms, while pelvic organ prolapse and pelvic pain were less common. The PFDI-20 is a useful tool for comprehensive symptom assessment, supporting early detection and appropriate management in clinical practice.